Ecovillages: worldview as an attempt of solving global ecological problems - Назаренко, М. С. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
Introduction, The article is dedicated to the concept of ecovillage as an extremely actual phenomenon in the situation of growing social conflicts and environmental crisis nowadays. The aim of the study is to attempt to analyze the worldview of this environmental movement and the eco-settlers’ ways of changing the world. For this purpose we need to realize the following tasks: 1) to find out what eco-settlements are, what their basic principles and principles are; 2) to distinguish philosophical elements that nourish a special attitude to the environment; 3) analyze what perceptions about eco-habitats exist in the conditions of lack of proper knowledge about them, and to find out what prevents from fully assessing their potential to socialize and improve the environmental situation in the world. Research methods. For this the author will use the observation method as well as the analytical method, involving in the theoretical part a number of practical cases explaining the activity and functioning of ecological settlements. Research results: Particular attention is paid to the model of the «circular economy», examples of its functioning in the world, in particular in the Ukrainian experience, are given. The concept of permaculture as a kind of experimental embodiment of ancient dialectics is also examined in detail. The basis of social relations in ecological settlements is analyzed – the theory of sociocracy, which is designed to create a sense of collective unity. The theory used by ecovillages makes such communities more mature and resilient in conflict situations. The ideology of simplification, as well as the approach to consumption in sustainable communities, which are characterized by conscious minimalism, is considered. Discussion. The article also discusses the widespread concept of ecovillages as a kind of utopia or a consequence of eschatological consciousness. The fallibility of this view is proved. As for conclusion, that is the statement about the possibility of solving the global through the local, because in the world view of eco-settlements, this possibility is embedded in the principles of permaculture. There are two common stereotypes about sustainable communities that allow us to look at our perceptions of this alternative way of living.